2001
DOI: 10.1051/0004-6361:20000248
|View full text |Cite
|
Sign up to set email alerts
|

Dissolving star cluster candidates

Abstract: Abstract. We present a list of 34 neglected entries from star cluster catalogues located at relatively high galactic latitudes (|b| > 15• ) which appear to be candidate late stages of star cluster dynamical evolution. Although underpopulated with respect to usual open clusters, they still present a high number density contrast as compared to the galactic field. This was verified by means of (i) predicted model counts from different galactic subsystems in the same direction, and (ii) Guide Star Catalog equal so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
91
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(99 citation statements)
references
References 23 publications
6
91
0
2
Order By: Relevance
“…De la Fuente Marcos (1998) has shown that our Galaxy should host several hundreds of thousands of open cluster remnants which have been disrupted by the Galaxy and by their own dynamical evolution (evaporation). Bica et al (2001) indeed observe several dissolving star cluster candidates.…”
Section: Introductionmentioning
confidence: 78%
“…De la Fuente Marcos (1998) has shown that our Galaxy should host several hundreds of thousands of open cluster remnants which have been disrupted by the Galaxy and by their own dynamical evolution (evaporation). Bica et al (2001) indeed observe several dissolving star cluster candidates.…”
Section: Introductionmentioning
confidence: 78%
“…An XDSS (second generation Digitized Sky Survey) blow-up of the concentration was shown in Fig. 4 of Bica et al (2001). We emphasize that the present set of stars related to the concentration is not BT's set of members.…”
Section: Introductionmentioning
confidence: 84%
“…Bassino et al (2000) find evidence of a possible remnant -M 73 (NGC 6994), but Carraro (2000) does not favour it. Bica et al (2001) presented 34 dissolving star cluster candidates which are located at relatively high galactic latitudes (|b| > 15 • ) and are underpopulated with respect to usual open clusters, but they possess a significant number density contrast as compared to the Galactic field. The distinction between an open cluster and a remnant is not obvious both observationally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations